Health literacy and cultural responsiveness of primary health care systems and services in Australia: reflections from service providers, stakeholders, and people from refugee backgrounds - Prince Peprah; Jane Lloyd; Mark Harris (BMC, 2023)
Abstract Background Primary health care [PHC] services with general practitioners (GPs) as the first point of access to health care services for people from refugee backgrounds in Australia can play a crucial role in building health literacy and promoting access to culturally appropriate services. To achieve equitable access and engagement, services and systems must be responsive to diverse health literacy and cultural needs. This study aims to explore how primary health services respond as a system and organisation to the health literacy and cultural needs of people from refugee backgrounds in Australia. Methods This exploratory qualitative study involved 52 semi-structured interviews among 19 Africans from refugee backgrounds, 14 service providers, including GPs and nurses, and 19 other stakeholders, such as service managers/directors. Participants resided in New South Wales, Victoria, and Queensland. Interviews were audio-recorded, transcribed, and coded into QSR NVivo 12. Data analysis was guided by reflexive thematic analysis. Findings Three interrelated themes were identified from the data relating to the health literacy and cultural responsiveness of PHC systems and services. The first theme, 'variable and ad hoc organisational response to health literacy and culturally responsive care,' demonstrated that some organisations did not systematically address the inherent complexity of navigating the health system nor the capacity of services and providers to respond to the cultural needs of people from refugee backgrounds. The second theme, 'individual provider responsibility,' captured the individual providers' interpersonal and relational efforts in supporting the health literacy and cultural needs of people from refugee backgrounds based on their motivation and adaptation. The third theme, 'refugee patient responsibility,' encapsulated people from refugee backgrounds' adaptations to and learning of the health system to navigate and access services. Conclusion Health literacy and culturally responsive practices need to be systematised by PHC organisations to be implemented and sustained over time. There is a need for diversity in the organisational leadership and health care workforce, organisational commitment, health literacy and culturally responsive care policies, provider training, and auditing practice as essential components of the change process. Engaging with refugee communities would allow services to focus on people from refugee backgrounds' needs by design.